Smartphones can improve adherence rates for TB treatment. (29th August 2019) - Cook, Rob; Lamont, Tara; Martin, Rosie
The study: Story A, Aldridge R, Smith C, et al. Smartphone-enabled video-observed versus directly observed treatment for tuberculosis: a multicentre, analyst-blinded, randomised, controlled superiority trial. Lancet 2019;393:1216-24. The study was funded by the NIHR Programme Grants for Applied Research programme (project number RP-PG-0407-10340). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000777/smartphones-for-tb-treatment-observation